Tomotherapy: Implications on Daily Workload and Scheduling Patients Based on Three Years' Institutional Experience. (June 2014) - Piotrowski, T.; Czajka, E.; Bak, B.; Kazmierska, J.; Skorska, M.; Ryczkowski, A.; Adamczyk, M.; Jodda, A.
Helical tomotherapy (HT) was introduced at the Greater Poland Cancer Centre (GPCC) inApril 2009. Retrospective analysis included data from the treatments performed for the first 656 patients treated with HT between May 2009 and May 2012 at the GPCC. In order to evaluate the implications on daily workload and scheduling of patients, stepwise regression and time analysis for each component of the overall treatment time, such as positioning, imaging, registration, and irradiation were performed. A detailed analysis included: (1) learning curves and optimized time needed for positioning and registration; (2) relation between irradiation time and parameters used for plan creation; and (3) average time of daily imaging. Theirradiation component has the highest influence on the overall treatment time (R = 0.911). The lowest influence was observed for the imaging (R = 0.670). The learning curve for positioning was 7 months while the reduction of the average daily time needed for registration was observed even after two years. The irradiation time strongly depends on the planning parameters. Changing the pitch from 0.215 to 0.287 for pelvic cancer cases decreased the average daily beam-on time per patient by about 2 minutes. Similar changes for head and neck reduced this time by 1.3 minutes. The limitation in the usage of 1cm field width only for complex cases, lower than 10 cm in the cranio-caudal direction, reduced the beam-on time per patient by 2 minutes. The average overall treatment time decreased from 21.5 minutesper patient in the first year of the HT usage to 13.8 minutes per patient in current practice . Our current practice shows that for a group of patients including mainly those with pelvis and head and neck cancers, the HT treatment takes approximately 15 minutes per patient allowing 40 patients to be treated within 10 hours.